Effect of Elicitors as Stimulating Substances on Sensory Quality Traits in Color Sweet Bell Pepper (Capsicum annuum L. cv. Fascinato and Orangela) Grown under Greenhouse Conditions - Jimenez-Garcia Sandra N.; Vázquez-Cruz Moisés A.; Miranda-Lopez Rita; Garcia-Mier Lina; Guevara-González Ramon G.; Feregrino-Perez Ana A. (Polish Journal of Food and Nutrition Sciences)
The effect of the application of salicylic acid (SA) and hydrogen peroxide (H2O2) was evaluated on sensory quality traits of two commercial sweet bell pepper varieties, Fascinato and Orangela, by descriptive sensory evaluation, principal component analysis (PCA), and Multivariate Analysis of Variance (MANOVA). A sensory descriptive lexicon was established for the sweet pepper and an intensity score was assigned for 25 sensory attributes in all the samples. Such intensity score was performed by twelve trained panelists. Among the results it was shown that foliar application of elicitors to pepper crop produced significant differences in sensory traits of the harvested fruits. MANOVA allowed detecting differences in aroma profile among treatments and varieties, showing important changes depending on the combination of elicitors applied on each variety. The principal component analysis (PCA), showed that the PC1 explained 81.02%, while PC2 explained 9.24% of the variance in the results. A strong correlation between varieties and treatments 2 (36 mM H2O2) and 4 (0.1 mM SA and 36 mM H2O2) with PC1 was observed. Treatments 2 and 4 were related to changes in aroma and flavor traits. Fascinato was more susceptible to the effect of elicitor than Orangela. Therefore, elicitor combinations used in this experiment were capable to improve sensory quality of peppers, and not only promote an increase in shelf life as previous studies have shown.